B. P. Shillaber papers - Shillaber, B. P. (Benjamin Penhallow), 1814-1890.
Autograph (1856 December 6) signed by B. P. Shillaber, Ruth Partington, and Ike (Partington); reply to an invitation (1881 November 2); and an ALS (1884 December 11) from Shillaber concerning a piece of his writing.
Editor and humorist. Also wrote under the name, Ruth Partington, a character in his writings.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: American wit and humor; Editors; Humorists